Variation in bucco‐palatal maxillary sinus width does not permit a meaningful sinus classification. Issue 12 (6th December 2018) - Bertl, Kristina; Mick, René‐Bernard; Heimel, Patrick; Gahleitner, André; Stavropoulos, Andreas; Ulm, Christian
Abstract: Objectives: The bucco‐palatal sinus width (SW) appears as relevant factor for graft consolidation after maxillary sinus (MS) floor augmentation. The present study aimed to assess (a) SW at different height levels of posterior teeth, (b) possible factors influencing SW, and (c) whether a simple/meaningful sinus classification based on SW is possible. Methods: The following parameters were recorded on computed tomographies of 76 edentulous and 86 partially edentulous maxillary quadrants displaying 383 tooth sites in total: (a) alveolar ridge height, (b) ‐area, (c) ‐width 2 mm apical to the alveolar crest, (d) ‐width at the sinus floor, and (e) SW and sinus area at a level 2, 4, 6, 8, and 10 mm above the sinus floor. The possible influence of gender, tooth position [i.e., premolar (PM); molar (M)], tooth‐gap extent, and residual alveolar ridge dimensions on SW was assessed. Further, based on percentiles of average values or on the frequency distribution of SW <10, 10–15, or >15 mm, it was attempted to classify the sinus at each given site into narrow, average, or wide. Results: Gender and tooth‐gap extent presented no relevant impact on MS dimensions; however, significant differences were observed among the various tooth positions regarding all evaluated parameters. The lower the residual alveolar ridge, the wider the MS at 4–10 mm height, while the wider the residual alveolar ridge, the wider the MS. Large variation in SW classes among the different height levels within the same tooth position and among tooth positions within the same person was observed, irrespective of the threshold applied. Further, at a MS height of 10 mm at PM1, PM2, M1, and M2, SW was <10 mm in 68%, 33%, 0%, and 7% of the cases, respectively, while in 3%, 21%, 65%, and 57%, respectively, SW was >15 mm. Conclusions: There is a large variation in SW depending on the height level within the sinus and on tooth position, which does not permit a simple/meaningful classification of each sinus as "narrow, " "average, " or "wide." Nevertheless, narrow sinuses (<10 mm) are rather prevalent in the premolar region, while wide sinuses (>15 mm) in the molar region; further, a wider and shorter residual alveolar ridge is associated with a wider SW.